2021
DOI: 10.3390/ijerph18094852
|View full text |Cite
|
Sign up to set email alerts
|

A Case Control Study on Serum Levels of Potential Biomarkers in Male Breast Cancer Patients

Abstract: The global incidence of breast cancer among men is steadily growing. Despite this, compared to female breast cancer patients, there are very few studies on biomarkers in male breast cancer patients. A cross-sectional case control study was carried out to determine the serum levels of melatonin, ghrelin, dopamine, serotonin, epinephrine, and GABA in male breast cancer. All the recruited patients were obese, old, and had recently been diagnosed with the disease. They had not received any treatment for the cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Ghrelin, a widely distributed peptide hormone, participates in a series of cancer progression (35); GHRL plays a vital role in carcinogenic potential, which was correlated with breast cancer, lung cancer, bladder cancer, and adrenal cancer (17)(18)(19)(20). There is an increasing evidence implicating an immunoregulatory role for ghrelin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghrelin, a widely distributed peptide hormone, participates in a series of cancer progression (35); GHRL plays a vital role in carcinogenic potential, which was correlated with breast cancer, lung cancer, bladder cancer, and adrenal cancer (17)(18)(19)(20). There is an increasing evidence implicating an immunoregulatory role for ghrelin.…”
Section: Discussionmentioning
confidence: 99%
“…found that ghrelin and its receptor (GHSR) were expressed in T cells and monocytes; ghrelin inhibited the expression of proinflammatory cytokines tumor necrosis factor alpha (TNF-a) and interleukin (IL)-6 and inhibited inflammatory reactions ( 12 ). It has been confirmed that the stomach was indeed not the only source of ghrelin ( 13 ); hypothalamus, hippocampus, pituitary gland, cortex, small intestine, and pancreas can also secrete a small amount of ghrelin ( 14 16 ), GHRL plays important roles in the development of tumors, and aberrant GHRL expression has been found in various cancers, such as breast cancer ( 17 ), lung cancer ( 18 ), bladder cancer ( 19 ), and adrenal cancer ( 20 ). At present, there were some researchers who found that ghrelin affects cancer cell proliferation, migration, and invasion through different signaling pathways ( 21 24 ).…”
Section: Introductionmentioning
confidence: 99%